Drought responses and adaptation in plants differing in life-form - Nour, Mudawi M.; Aljabi, Hanadi Riyad; AL-Huqail, Arwa Abdulkreem; Horneburg, Bernd; Mohammed, Afrah E.; Alotaibi, Modhi O. (Frontiers in Ecology and Evolution, 2024)
Drought is considered one of the most critical abiotic environmental stresses and limits plant growth, development, and productivity. It constitutes a real threat to humanity, especially in dry areas worldwide. Plants manage the negative effects of drought through a complex set of related mechanisms. Knowledge of plant responses and adaptation is more meaningful in plant breeding and genetics for improving drought resistance species. This review will focus on drought response mechanisms and drought adaptation, providing examples from plant species differing in their life-form, including herbaceous and woody plants. Additionally, the potential role of enhancing plant drought responses will be emphasized. This review is of potential significance to researchers and those who wish to obtain a glimpse into plant behavior under drought conditions.